Climate Change and the Way to Sustainable Energy Use: Array - Turtureanu, Anca; Chitu, Florentina; Cretu , Carmen Mihaela; Dorobăț, Leonard Magdalin; Dobrescu, Codruța Mihaela (Acta Universitatis Danubius. Œconomica, 2021)
Climate change is a pressing threat and poses great risks to the global economy. One of the consequences of global warming is climate change, the most visible effects of which are melting polar caps, rising sea levels - some Pacific islands are already disappearing, and their inhabitants are already to emigrate to other islands. safer - increased frequency of extreme weather events, droughts, forest fires, floods, ecosystem degradation and biodiversity loss. In other words, global warming "disrupts" the climate. It should be noted that the climate has never been stable; In the history of our planet, the climate has always changed, but the current climate crisis is unique in terms of speed, intensity, causes and, above all, consequences. Anthropogenic climate change has already led to substantial changes in the environments and extremes of many climate variables. Additional climate change is now inevitable, but its speed and scale depend on the success of global mitigation policies. Romania has committed through the Integrated National Plan in the field of Energy and Climate Change 2021-2030 to reduce by 2030 by 43.9% ETS (EU Emissions Trading System) emissions compared to 2005 values ​​and to increase the global share of energy from renewable sources in gross final energy consumption by 30.7%.